Studying the impact of zein microfibers on the physicochemical and microstructural properties of bi-gels based on ι-carrageenan hydrogels and beeswax oleogels - Mojtaba Rezaei; Sara Naji-Tabasi; Behrouz Ghorani; Bahareh Emadzadeh (Current Research in Food Science)
This research presents a novel bi-gel system formed by combining zein microfiber -reinforced carrageenan hydrogels and beeswax oleogels. The main objective is investigating the impact of the interplay between zein microfibers, ι-carrageenan hydrogels, beeswax oleogels on the properties of bi-gels. The study focused on bi-gel formulations combining beeswax oleogel and carrageenan, both plain and with zein microfibers. Different ratios of oleogel to ɩ-carrageenan hydrogel and oleogel to reinforced ɩ-carrageenan hydrogel were established: 5:95, 10:90, 15:85. The designed bi-gels exhibited semi-solid gel properties in rheological analysis, with increased oleogel content enhancing firmness, storage modulus, and loss modulus (G' < G″, p < 0.05). The incorporation of oleogel in the bi-gel substantially increased its consistency from 131 (g.s) to 668 (g.s) in the bi-gel containing 0.5% zein microfiber, 10% oleogel, and 90% hydrogel. FTIR results suggested that the bi-gels were formed through physical interactions without covalent cross-linking. Microfibers had a positive effect on the textural characteristics of bi-gels. The hardness of bi-gels increased from 13.26 to 35.12 g to 31-93-64.14 g after addition of microfibers. The BGZ10 formulation, consisting of 10% oleogel and 90% zein-reinforced hydrogel, showed the highest consistency among samples, with measurements of 668.48 ± 3.53 (g.s) and a G′ value of 291000 ± 91.27 (Pa) (P < 0.05). Additionally, the BGZ10 formulation displayed the highest complex viscosity, measuring at 47300 ± 20.73 (P < 0.05). The thermal stability of bigel considerably increased by cooperation fibers in hydrogel. The developed bi-gels demonstrate significant potential for substituting conventional solid fats and introducing distinctive visual characteristics in various food products.